2022
DOI: 10.3390/cryst12010098
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of UV Dye-Sensitized Solar Cells Based on Water Electrolyte: A New Insight for Wavelength-Selective Greenhouse

Abstract: The optimization of the photoactive electrode based on TiO2 with a complex architecture for UV dyes along with water-based electrolyte has successfully allowed us (i) to obtain a photovoltaic efficiency of the dye-sensitized solar cell with 1.45 times higher than the best efficiency reported for synthetic dye and 3 times for curcumin dye so far; (ii) transparency on the entire Photosynthetic Active Radiation domain; (iii) preserving high efficiency for lighting 1 sun (summer) and shading, especially for 60 mW/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The beneficial positive evolution of the temperature coefficient for the short circuit current ( α ) for all yellow DSSCs is due to its high absorption of UV radiation (355–400 nm), close to 98% (ref. 16 and 19) highlighted in the previous work. Together with TiO 2 , the yellow dye also acts as a filter extending UV absorption domain with direct effect on decreasing the depletion of I 3 − from the electrolyte, and thus, no reduction in J SC was observed by diffusion limitation.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The beneficial positive evolution of the temperature coefficient for the short circuit current ( α ) for all yellow DSSCs is due to its high absorption of UV radiation (355–400 nm), close to 98% (ref. 16 and 19) highlighted in the previous work. Together with TiO 2 , the yellow dye also acts as a filter extending UV absorption domain with direct effect on decreasing the depletion of I 3 − from the electrolyte, and thus, no reduction in J SC was observed by diffusion limitation.…”
Section: Resultsmentioning
confidence: 66%
“…DSSCs without and with a rutile/anatase TiO 2 -based light-scattering layer (named DSSC_2 and DSSC2_RLS) were achieved according to our previous work. 19 In this case, the DSSC_2 photoanode characterized by 0.75 μm thickness also consists of 3 layers arranged as follows: (i) the first compact layer of TiO 2 as a blocking layer, obtained as above; (ii) the second layer consists of TiO 2 nanoparticles crystallized in the anatase form and obtained by a sol–gel method; and (iii) the final treatment of 40 mM TiCl 4 applied on the surface of the photoanode, and further sintered at 450 °C for 1 h. As stated above, the DSSC2_RLS photoanode characterized by 3.75 μm thickness is composed of 4 layers, 3 layers previously presented, and another layer placed before the TiCl 4 treatment step that contains a mixed rutile/anatase polymorphic phase-based TiO 2 as a scattering layer. All other steps for the fabrication and assembly of DSSC components follow the same pattern as presented above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 This would represent an evident product sustainability and safety advantage given the integration of DSSCs with portable devices; also, water would lead to better solvent properties towards more redox couples and additives, as well as greater durability due to reduced electrolyte evaporation. 42,43 This prompted researchers to develop materials for the so-called aqueous DSSCs, proposing new formulations of liquid and gel-polymer electrolytes, [44][45][46][47] aqueous stable dyes, [48][49][50] photoanode treatment protocols, [51][52][53] platinum-free counter electrodes 54,55 to further reduce the cost and impact of this technology. In these first years of research activity, maximum photovoltaic performances of the order of 6-7% have been achieved 56,57 and further experimental and computational investigations are currently underway to try to reduce the efficiency gap with respect to the corresponding DSSCs manufactured with nitrilesbased organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of hydrophobic dyes with a water-based electrolyte is mandatory. Different research groups have recently demonstrated that a low amount of water (5–20%) in the electrolyte composition decreases the TiO 2 lattice disorder, improving the photo-current density [ 13 , 14 , 15 ]. The incorporation of a small amount of water works as a doping strategy, incorporating oxygen from water into TiO 2 oxygen vacancies, leaving hydrogen atoms exposed on their surface; this results in a band-edge shift toward more positive potentials due to the positive charge accumulation at the TiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%